Plato's Sun : An Introduction to Philosophy - Lawless, Andrew (Book collections on Project MUSE., 2005)
Writing an introductory text for philosophy is an exceedingly difficult task. The discipline has spent a century or more in existential crisis with the attack on metaphysics dating back at least to Nietzsche and carried forward in different ways by Heidegger, Wittgenstein, and Derrida, to name a few. This constant upheaval has precipitated a climate of self-doubt that goes to the core of philosophy, the result being a strange discipline with many of its most illustrious names proudly announcing its demise.In Plato's Sun, Andrew Lawless takes on the challenge of creating an introductory text for philosophy, arguing that such a work has to take into account of the strangeness of the field and divulge it, rather than suppress it beneath traditional certainties and authoritative pronouncements. Lawless writes within the shadow of post-modern anti-metaphysical skepticism, introducing some of the principal areas of philosophy: metaphysics, epistemology, logic, ethics, and language.Lawless's concern is not to resolve the issues he raises so much as to set them out in a way that lets the reader experience something of the philosopher's struggle. In so doing, Lawless holds fast to the Socratic vision of philosophy as a process of inquiry that values questions above answers, pushing the inquirer beyond his or her answers. With numerous pedagogical features including glossaries of names and key terms, suggested readings, and short chapter summaries, Plato's Sun will be an essential text to new students of philosophy and an important aid in teaching the subject.